Seven Faces of a Fatwa: Organ Transplantation and Islam - Ali, Mansur (Religions, 2020)
A new fatwa was announced by the British National Health Service (NHS) in June 2019 to clarify the Islamic position on organ donation. Additionally, the NHS promotional material presents brief arguments for and against organ donation in Islam. However, to date, research into the various fatwas on organ donation is required. This article goes beyond the dichotomous positions mentioned by the NHS and goes on to explore and summarise seven conflicting views on the issue extrapolated from an exhaustive reading of fatwas and research papers in various languages since 1925. Our discussion is circumscribed to allotransplant and confined to the gifting of organs to legally competent adult donors at the time of consent. These arguments include an analysis of the semantic portrayal of ownership in the Qur’an; considering the net benefit over the gross harm involved in organ donation; balancing the rights of the human body with the application of the rule of necessity; understanding the difference between anthropophagy and organ transplantation; understanding of death, and the conceptualisation of the soul. We argue that, given the absence of clear-cut direction from Muslim scripture, all seven positions are Islamic positions and people are at liberty to adopt any one position without theological guilt or moral culpability.